The Influence of Work Environment on Employee Performance with Work Spirit as an Intervening Variable - Jopinus Saragih (International Journal of Management Research and Economics, 2023)
The results of this research show. (1) It can be seen that the value of the adjusted R square is 0.130 or 13.0%. This shows that the work environment (X) can explainspirit at work(Z) is 13.0%, the remaining 87.0% (100% - 13.0%) is explained by other variables outside this research model. (2) The results of the t test (Partial) show that tcount (7.652) > ttable (2.042), likewise with a significance value of 0.00 < 0.05, it can be concluded that the first hypothesis is accepted, meaning that the work environment variable(X) has a positive and significant effecton work morale (Z).(3) The results of the t test (Partial) show that the value of tcount (3.955) > ttable (2.042), and the significance value is 0.00 < 0.05, so it can be concluded that the second hypothesis is accepted, meaningwork environment(X) has a significant effecton employee performance (Y). (4) The results of the path analysis test show that the direct influence of variable X on variable Y2 is 0.586. Meanwhile, the indirect influence through variable.